THE PHENOMENON OF GENERATION Z SEEKING VALIDATION AND SELF-RECOGNITION ON SOCIAL MEDIA: A USES AND GRATIFICATIONS APPROACH - Dian Nova Safitri; Farhan Indra (Journal Analytica Islamica, 2026)
This research is motivated by the increasing use of Instagram among Generation Z, which not only functions as a medium for communication and entertainment, but also as a digital space for building identity, gaining self-validation, and gaining self-recognition. Different from previous research that tends to emphasize the impact of social media use on users' psychological conditions, this study offers novelty by positioning Generation Z as active, selective, and conscious media users in utilizing Instagram to fulfill their psychological and social needs. This study aims to understand the meaning of Instagram use, motives for seeking self-validation, and forms of self-recognition built through digital interactions. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation of six informants aged 18–25 who actively use Instagram. The results show that Instagram is interpreted as a space for self-expression, personal branding, digital identity formation, as well as a medium for obtaining social responses through likes and comments. Positive responses can increase self-confidence, motivation, and feelings of appreciation, while minimal responses encourage self-evaluation of uploaded content. From the Uses and Gratification perspective, Instagram use is dominated by the need for personal integration and social integration. The scientific contribution of this research lies in strengthening the understanding that the search for self-validation and self-recognition in Generation Z is not merely a passive result of social media use, but rather part of an active process in managing image, identity, and social relations in the digital space.